Postcolonialism Cross-Examined Multidirectional Perspectives on Imperial and Colonial Pasts and the Neocolonial Present - Albrecht, Monika (Taylor & Francis, 2019)
Taking a strikingly interdisciplinary and global approach, Postcolonialism Cross-Examined reflects on the current status of postcolonial studies and attempts to break through traditional boundaries, creating a truly comparative and genuinely global phenomenon. Drawing together the field of mainstream postcolonial studies with post-Soviet postcolonial studies and studies of the late Ottoman Empire, the contributors in this volume question many of the concepts and assumptions we have become accustomed to in postcolonial studies, creating a fresh new version of the field. The volume calls the merits of the field into question, investigating how postcolonial studies may have perpetuated and normalized colonialism as an issue exclusive to Western colonial and imperial powers. The volume is the first to open a dialogue between three different areas of postcolonial scholarship that previously developed independently from one another: • the wide field of postcolonial studies working on European colonialism, • the growing field of post-Soviet postcolonial/post-imperial studies, • the still fledgling field of post-Ottoman postcolonial/post-imperial studies, supported by sideways glances at the multidirectional conditions of interaction in East Africa and the East and West Indies. Postcolonialism Cross-Examined looks at topics such as humanism, nationalism, multiculturalism, nostalgia, and the Anthropocene in order to piece together a new, broader vision for postcolonial studies in the twenty-first century. By including territories other than those covered by the postcolonial mainstream, the book strives to reframe the "postcolonial" as a genuinely global phenomenon and develop multidirectional postcolonial perspectives.